Pengaruh Penggunaan Video Pembelajaran IPA Terhadap Minat Belajar Siswa Kelas III SD Inpres Lanraki 2 Kecamatan Tamalanrea Kota Makassar - Hamzah Pagarra; Nur Abidah Idrus (Publikasi Pendidikan, 2018)
The objectives of this research are 1) To know the description of the usage of learning media video of IPA class III SD Inpres Lanraki 2 Subdistrict Tamalanrea Makassar City, 2) To know the description of student interest in third grade SD Inpres Lanraki 2 Tamalanrea Sub-District Makassar City, 3) learning videos of science to the interest of third grade students of SD Inpres Lanraki 2 District Tamalanrea Makassar City. This study used a quantitative approach. In this approach the data will be analyzed quantitatively by using statistics to test the hypotheses that have been prepared. The type of research used in this research is Pre- Experimental with the design of One Group Pretest-Posttest design research. Population and sample of this research is third grade student of Inpres Lanraki 2 2016/2017 academic year. Data collection techniques in this study are: questionnaires, observation sheets, and documentation. The data analysis technique used in this research is descriptive statistical analysis and inferential statistical analysis. To see the difference, the data were analyzed using Paired Sample t-Test. Based on the results of hypothesis testing with inferential statistics shows there is a significant influence of the use of learning video media on the interest of learning IPA.